Asketiske praksisser i Koranen: Vigilien som case - Christiansen, Johanne Louise (Religionsvidenskabeligt Tidsskrift, 2016)
In this article, I propose that Peter Sloterdijk’s etymological definition of áskesis as an ‘exercise’ is useful when approaching the Qur’ānic attitude(s) to ascetic practices, including in particular the text’s references to vigils. From a close reading of two passages in sūrat l-muzzammil (Q 73:1-9, 20), I argue for a chronological development in the Qur’ānic invitations to vigil practices. In this way, the Qur’ānic articulations of vigils can be understood as two types of ascetic ‘training programmes’, developing from the Prophet’s own extraordinary initiation practice to a more general ‘maintenance’ practice for the ordinary believer. Such a development appears to be consistent with the overall historical frame of Muḥammad’s prophetic career. By opening for a broader understanding of ‘asceticism’, the Qur’ān can be seen as taking part in a general ascetic tendency of the Axial Age.